A Pragmatic Study of Bullying in some Schools in Baghdad: A Comprehensive Analysis of Language Use and Power Dynamics (Journal of the College of Education for Women, 2025)
Bullying in educational environments is a widespread problem that is typified by aggressive actions and power disparities between people. This study explores a topic that has not gotten enough attention in the literature: the practical implications of bullying among Baghdadi students. Through the examination of data from many educational settings, the study seeks to address the following queries: Which kinds of bullying do students experience? What practical methods do students use to bully their classmates? An eclectic model was used to address these issues, and a survey of 100 randomly chosen students from seven hundred ones in various schools was administered. Of these, thirty students reported having been bullied. This investigation sheds light on the various tactics bullies use to intimidate and cause harm to their peers in educational settings. The results help create intervention tactics that are more successful in stopping bullying and fostering a more secure and encouraging learning environment in schools.